Studies on pretreatment and biosugars recovery from oil palm frond juice - Faatihah, Mohamad Asri (2014)
Oil palm (Elaeis guineensis jacq) frond (OPF) has a great potential to be commercialized due to its abundance as an oil palm solid wastes that are generated during oil palm agriculture and harvest. OPF juice has been identified as a good candidate to replace pure or technical grade sugars for the production of value-added products. Recently, it has been reported that OPF juice can be used as the sole renewable carbon source for the production of poly (3-hydroxybutyrate), P(3HB). In order to further evaluate the future prospect of OPF juice as fermentation feedstock, in-depth investigation on the bioconversion of OPF juice to produce other valuable products such as lactic acid and bioethanol will be the focus of future research project. Prior to that, OPF juice has to be treated to remove the precipitate as well as others impurities. This study has to be done at the first place in order to further enhance the sugars recovery to increase the concentration and purity of the renewable sugars contained in the OPF juice. In order to achieve this objective, three different pre-treatment processes including chemical treatment with calcium chloride, heat and chemical treatment with hydrogen peroxide and activated carbon adsorption was applied. The process parameters obtained from sugar analysis provided an insight information about the effect of the different pretreatment methods on sugar content in OPF juice. The treated juice was subjected to further process which is purification and recovery using conventional method i.e., crystallization and spray drying